Missing â€˜Apu’ in present Global Childhood and its impact - Adhikari, Harasankar (Innovare Journal of Social Sciences, 2017)
This short communication tried to compare today's childhood with APUâ€, childhood during colonial rule of India. Familial and societal changes are the prime cause of changing childhood and it may be considered as an effect of globalisation. Parenting and single child politics are the cause violent and deviant childhood. So, up-bringing process of child should not depend on materials.